Tinjauan Yuridis Terhadap Hubungan Kerja Tindakan Penahanan Ijazah Pekerja Oleh Perusahaan Berdasar Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - I Made Chossy Narayanan; I Wayan Novy Purwanto (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
The motivation behind this paper is to decide the game plan of business relations that outcome in the detainment of a laborer's confirmation by the organization as far as Law Number 13 of 2003 concerning Manpower. Utilization of a confirmation as an assurance of work in the work arrangement between the organization and the provisional laborers. This study utilizes a standardizing legitimate technique and this examination will utilize three ways to deal with break down the issue, to be specific the legal methodology, the applied methodology, and the recorded methodology. This kind of exploration is standardizing juridical examination. This examination is an exploration on lawful synchronization. In this review, the creators utilized library research. Wellsprings of information utilizing essential information, optional information, and tertiary information. The creator gathers information utilizing different libraries, print broad communications, and web media.